2019
DOI: 10.1140/epjb/e2019-100147-y
|View full text |Cite
|
Sign up to set email alerts
|

Generalized spin-orbit torques in two-dimensional ferromagnets with spin-orbit coupling

Abstract: Based on the spinor Boltzmann equation, we obtain the continuity equations of charge and spin accumulation in two-dimensional ferromagnets with Rashba or Dresselhaus spin-orbit coupling, in which the spin diffusion equation (the continuity equation of spin accumulation) gives the spin-orbit torques that have an extra term of charge density gradient that is paid little attention in previous studies. Numerical results indicate this term plays an important role in inhomogeneous systems. In order to study the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The spin–orbit torque is the result of s–d interaction between the local magnetic moment and spin accumulation of conduction electrons, and it is always expressed as [ 23 , 24 ]: where is the spin accumulation and can be calculated by definition [ 4 , 15 ]: According to the distribution function above, the spin accumulation along the y axis is Compared to Equation ( 9 ), is directly proportional to . , and this specific value is a constant which has no connection with the band structure and temperature.…”
Section: Spin–orbit Torquementioning
confidence: 99%
See 1 more Smart Citation
“…The spin–orbit torque is the result of s–d interaction between the local magnetic moment and spin accumulation of conduction electrons, and it is always expressed as [ 23 , 24 ]: where is the spin accumulation and can be calculated by definition [ 4 , 15 ]: According to the distribution function above, the spin accumulation along the y axis is Compared to Equation ( 9 ), is directly proportional to . , and this specific value is a constant which has no connection with the band structure and temperature.…”
Section: Spin–orbit Torquementioning
confidence: 99%
“…Thus, the current and spin–orbit torque are both manifestations of the non-equilibrium transport properties of the SOC system, there must be some relations between them. Literature have showed that the magnitude of spin–orbit torque is often proportional to the current density [ 12 , 13 , 14 , 15 ]. Because the spin accumulation and charge current are proportional to the external electric field under linear transport conditions, the ratio depends on the band structure of the system [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the above Hamiltonian, we can derive the spinor Boltzmann equation, [22,23] based on the NEGF formalism, as…”
Section: Smm Heavy Metal Layermentioning
confidence: 99%
“…[21] Furthermore, the spin-polarized transport with spinorbit interactions was also studied by the spinor Boltzmann equation. [22,23] In this letter, we study the magnetization reversal of SMMs by spin-polarized current. The system is schematically depicted in Fig.…”
mentioning
confidence: 99%
“…When the inversion symmetry and spin-orbit coupling break together it leads to coupled spin and valley physics in ML-MoS 2 [22]. Yang demonstrates that spin-orbit interaction provides an alternative and efficient way to handle the magnetization via spin-orbit torques [23]. It can be obtained that the transmission probability for transport is an oscillating function and depends on incident angle, barrier height, and the incident energy of electrons and that, the quasi-bound states in the well regions (outside the barriers) are responsible for the oscillating behavior.…”
Section: Introductionmentioning
confidence: 99%